Gardening as a physical activity for health in older adults - Park, Sin-Ae (Kansas State University, 2007)
The objectives of this study were to determine exercise intensity of common gardening tasks in older adults and to investigate if older gardeners meet the physical activity (PA) recommendations (intensity and time) through their daily gardening. Kinds of gardening tasks, body postures, and bodily pain while gardening of older gardeners were investigated and the possibility of gardening as a predictor for a physically active lifestyle and life satisfaction in older adults was determined. Older participants were randomly recruited from the community of Manhattan, KS. To determine the exercise intensity of gardening, the heart rates of older adults were measured by radiotelemetry during gardening or garden tasks, and then oxygen uptake and energy expenditure were measured via indirect calorimetry using a submaximal graded exercise test. Overall health conditions by the Short Form 36 Health Survey (SF-36), hand functions by hydraulic hand dynamometer and pinch gauge, and bone mineral density (BMD) by dual-energy x-ray absorptiometry were measured. An observational study and weekly logs were conducted to study kinds of gardening, postures, and bodily pain of older gardeners. The Community Healthy Activities Model Program for Senior (CHAMPS) questionnaire was used to measure leisure-time PAs (frequency per week of all PAs and calories expended per week in all PAs). In conclusion, the nine gardening tasks were found to be low to moderate intensity PA in healthy older adults (1.6 ± 3.6 METs). Gardening observed was moderate intensity (3.8 ± 1.4 METs) PA in older adults and the subjects met the PA recommendation, which is at least 30 minutes of moderate intensity PA on most days of the week through their daily gardening (moderate intensity; average 33 hrs/wk in May and 15 hrs/wk in June and July). The older gardeners showed higher values for hand function and some SF-36 domains (physical function, bodily pain, and physical summary) than older non-gardeners. Gripping, stooping, lifting, stretching, walking, standing, kneeling, sitting, and squatting were observed while older adults gardened and lower back pain was the main bodily pain reported. Furthermore, gardening was found to be a predictor for leading a physically active lifestyle and high life satisfaction in older adults.
Keywords: Metabolic equivalent; Indirect calorimetry; Hand function; Bone mineral density; The Short Form 36 Health Survey (SF-36); The Community Healthy Activities Model Program for Senior questionnaire (CHAMPS questionnaire); Agriculture, General (0473); Health Sciences, General (0566)